THE ECONOMY OF TRANSACTION COSTS IN FAMILIAR AGROINDUSTRIES IN NORTH OF RIO GRANDE DO SUL - Silveira, Jaqueline Patrícia; Universidade Federal do Rio Grande do Sul (2019)
The study analysed as main objective to analyze the structures of governance and the coordination mechanisms adopted by the familiar agroindustries and their alignments with the theoretical assumptions. Therefore the theoretical approach of the New Institutional Economy and Economy of Transaction Costs - TCE was used. The exploratory-descriptive research was delineated through multiple case studies using qualitative and quantitative techniques. The study was developed in Northern Rio Grande do Sul State, where eleven familiar agroindustries were analized. The data were generated through semi-structured interviews, observation and field diary and analyzed with the support of descriptive statistics and Comparative Discrete Structural Analysis – CDSA. . The results show that most of the familiar agroindustries studied, seven cases, adopts a structure of market governance. Two of them use an hybrid governance form and the other two cases characterize hierarchical governance. The transactions present high asset specificity, recurrent frequency, low uncertainty, little opportunism and little limited rationality. Therefore, in applying CDSA it is assessed that even not being the most appropriate structure, familiar agroindustries are getting success in their transactions and this is due to the coordination mechanisms adopted, with emphasis on trust.